ANALISIS PUISI “RAHASIA HUJAN” KARYA HERI ISNAINI DENGAN MENGGUNAKAN PENDEKATAN MIMETIK - Nurlaela Tussaadah; Teti Sobari; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Poetry is an imaginative literary work, which analogizes meaning with other expressions so that the meaning contained in poetry is hidden behind aesthetic and fictional words that not everyone understands the direction and purpose of the poem delivered. Poetry is not easily understood by the reader at a glance because the language is broad and the meaning is difficult to interpret, therefore a reader must have the knowledge in studying poetry literary works in order to understand the meaning conveyed from the poem. The poem "Rahasia Hujan" by Heri Isnaini is formed from a unique and simple language order but has a broad meaning and makes readers interested in his work. The unique and beautiful language is an attraction and makes Heri Insaini's poetry into research material. The purpose of this study is to analyze the meaning in the poem entitled "rahasia hujan" by Heri Isnaini and convey the contents in detail of the poem so that the reader can know the meaning conveyed through this research. This research is also useful for readers to further develop literary works in the form of poetry. The method used in this study uses a qualitative method that examines the contents of the meaning of the poem "Rahasia Hujan". In addition poetry in this study was dissected using a mimetic approach. Mimetic is an approach in literary criticism about imitation or fiction of real life.